2021
DOI: 10.5194/cp-17-1119-2021
|View full text |Cite
|
Sign up to set email alerts
|

A data–model approach to interpreting speleothem oxygen isotope records from monsoon regions

Abstract: Abstract. Reconstruction of past changes in monsoon climate from speleothem oxygen isotope (δ18O) records is complex because δ18O signals can be influenced by multiple factors including changes in precipitation, precipitation recycling over land, temperature at the moisture source, and changes in the moisture source region and transport pathway. Here, we analyse >150 speleothem records of the Speleothem Isotopes Synthesis and AnaLysis (SISAL) database to produce composite regional trends in δ18O in monsoon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 141 publications
1
11
0
Order By: Relevance
“…Our study shows more depleted δ 18 O p in both annual and summer over East Asia during the LGM relative to the PI, well consistent with previous paleoclimate reconstruction and modeling (Eagle et al, 2013). However, these results contrast with recent geological evidence that indicated more enriched δ 18 O p over East Asia during the LGM (Parker et al, 2021), which appears to be supported by previous modeling studies that suggested an enrichment of δ 18 O p in response to precipitation deficit over East Asia due to a weakened EASM during the LGM (Hoffmann & Heimann, 1997;Jasechko et al, 2015). Nevertheless, this "amount effect" is challenged by increasing evidence verifying that changes in δ 18 O p over East Asia largely reflect changes in water vapor source and pathway instead of local precipitation amount (Huang et al, 2018;Pausata et al, 2011).…”
Section: δ 18 O P Changes Between the Lgm And Pisupporting
confidence: 84%
See 1 more Smart Citation
“…Our study shows more depleted δ 18 O p in both annual and summer over East Asia during the LGM relative to the PI, well consistent with previous paleoclimate reconstruction and modeling (Eagle et al, 2013). However, these results contrast with recent geological evidence that indicated more enriched δ 18 O p over East Asia during the LGM (Parker et al, 2021), which appears to be supported by previous modeling studies that suggested an enrichment of δ 18 O p in response to precipitation deficit over East Asia due to a weakened EASM during the LGM (Hoffmann & Heimann, 1997;Jasechko et al, 2015). Nevertheless, this "amount effect" is challenged by increasing evidence verifying that changes in δ 18 O p over East Asia largely reflect changes in water vapor source and pathway instead of local precipitation amount (Huang et al, 2018;Pausata et al, 2011).…”
Section: δ 18 O P Changes Between the Lgm And Pisupporting
confidence: 84%
“…Particularly in the Indian Peninsula and Indochina Peninsula, both regions showed dramatic depletion of δ 18 O p during the LGM (gray bars in Figure 3a) in response to heavy rainfall (gray bars in Figure 3b). The δ 18 O p changes spatially lagged behind the precipitation changes, suggesting that strong rainout due to heavy rainfall has a significant effect on δ 18 O p drop (Maher & Thompson, 2012; Parker et al., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Critical understanding of hydroclimate indication in rainfall isotopes of Southeast Asia remains lacking. Paleoclimate studies have mainly associated changes of rainfall isotopes in this region with rainfall amount 60 , moisture transport 61,62 , moisture convergence 16 and global ocean δ 18 O variance with glaciation 43 . In our iTraCE results, annual and JJA simulation between 20 ka and 10 ka suggest positive δ 18 O loading corresponding to decreased rainfall in Sumatra and southern Borneo; however, most regions of Sumatra and Borneo suggest decreased spring and autumn rainfall corresponding to negative δ 18 O (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…ECHAM5-wiso has been used extensively within the paleoclimate field, as well as for present time (for example, Werner et al, 2016;Langebroek et al, 2011;Goursaud et al, 2018). The fully coupled version of the model ECHAM5/MPI-OM ESM has very good agreement with both present-day isotope observations from the GNIP database, as well as with ice core 5 and speleothem proxies during mid-Holocene (MH, Comas-Bru et al, 2019), last glacial maximum (LGM Werner et al, 2016;Comas-Bru et al, 2019), and for last interglacial (Parker et al, 2021). Both in the ESM and with the atmospheric component (ECHAM5-wiso), a warm bias in the model is found over high-latitudinal regions, especially over Greenland and Antarctica (Werner et al, 2011(Werner et al, , 2016 and has been attributed to the coarse spatial resolution in the atmospheric component of the model (Werner et al, 2016) resulting in an underestimation of isotope depletion in these regions.…”
Section: Echam5/mpi-ommentioning
confidence: 92%